Génétiquement indéterminé - Pouteau , Sylvie (éditions Quae, 2007)
"Contemporary biology is called to accommodate the idea that while DNA is involved in the formation of an individual, the other constituents of the organism or of its environment are also determining factors. Nothing is ""programmed"" as such, and the challenge is to understand how the whole is assembled and structured. Five researchers from different scientific horizons here provide new and complementary insights into the singularity and auto-organization of living systems. The book includes a discussion glossary covering around thirty key notions, from adaptation to variability."